2022
DOI: 10.3390/su14074240
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health and Socioeconomic Status in Old Age: The Role of Gender and the Moderating Effect of Time and Welfare Regime in Europe

Abstract: Research has shown that health status and self-rated health (SRH) are correlated not only with age and gender but also with socioeconomic determinants, such as income, education, and employment status, in the course of life and in late life. Much less investigated, however, are gender differences in the association between socioeconomic factors and SRH and how the connection differs among the European welfare state regimes. This study examines the association between SRH and socioeconomic status in later life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…We elicited health information by asking the participants to rate their general health from 1 (very bad) to 5 (very good). This subjective general state of self-reported health has frequently proved to be a valid indicator of general physical health and a good indicator of morbidity and mortality (Kaplan, et al, 1996; Tur-Sinai et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…We elicited health information by asking the participants to rate their general health from 1 (very bad) to 5 (very good). This subjective general state of self-reported health has frequently proved to be a valid indicator of general physical health and a good indicator of morbidity and mortality (Kaplan, et al, 1996; Tur-Sinai et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In the European context, there exists a demographic predominance of women over men, underscoring the significance of upholding gender parity and ensuring equivalent rights for all individuals (Tur- Sinai et al 2022). This limitation of fundamental liberties can be construed as a direct impediment to the genuine economic empowerment of women.…”
Section: Introductionmentioning
confidence: 99%
“…tudies have shown that women generally report a lower self-rated health compared to men, but this di erence seems to decrease with age [22 ,229]. However, a recent longitudinal study using HAR panel data observed a consistent female disadvantage in self-rated health among older uropean adults aged 65 years at baseline and ten years later [230].…”
Section: Introductionmentioning
confidence: 99%